Community Empowerment: Processing Household Organic Waste into Compost Using the Takakura Technique: Pemberdayaan Masyarakat: Mengolah Sampah Organik Rumah Tangga Menjadi Pupuk Kompos dengan Teknik Takakura - Anis Rosyiatul Husna; Pipit Festy Willianarti; Ine Dzulfitriyanti Putri; Rahma Nadine Az-Zahra (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2023)
Household organic waste is produced from household activities every day. This garbage contains high water and rotten youth. High volume causes a buildup that pollutes the environment and becomes a disease outbreak.  Improper management techniques can have negative impacts on health and the environment. An alternative to processing organic waste generated from household activities is composting, which turns household waste into compost. The process of composting can be done with the Takakura technique. The activities aimed to increase community knowledge in household organic waste management and provide skills in utilizing organic waste into compost using the Takakura method for one week. The methods used were education, training, and assistance in making compost using the Takakura method to residents and health cadres of RW 06 Sutorejo Village, Mulyorejo, Surabaya, totaling 14 people. The activity results showed that community and health volunteers could understand household organic waste and composters and could make compost from household organic waste using the Takakura method. This change in knowledge is evidenced by the increase in before and after education and the increase in participants' skills in making compost. Making compost from organic waste with the Takakura method is economical for every citizen and does not require high costs. Based on this service activity, continuous socialization and assistance are needed for residents to utilize household organic waste.